Pengaruh Kualitas Pelayanan Dan Penetapan Harga Terhadap Kepuasan Konsumen Ruwang Coffeehouse Bekasi Pada Tahun 2023 - Sumidartini, Ai Netty; Khuzaifah, Nadia (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to determine the effect of Service Quality and Pricing on Consumer Satisfaction at Ruwang Coffeehouse. The sample in this study were customers at Cafe Ruwang Coffeehouse. This data collection was carried out by distributing questionnaires with a sample of 110 respondents. The method used in this study uses quantitative methods. This study also uses data analysis techniques in the form of analysis Descriptive, Questionnaire Test, Classical Assumption Test, Multiple Linear Regression Test. Processing in this study uses IBM SPSS version 21. The results of this study are Service Quality and Pricing have a significant effect on Customer Satisfaction of Ruwang Coffeehouse Bekasi 2023 customers partially or simultaneously.